An integrative water quality evaluation in two surface water bodies from a tropical agricultural region in Cartago, Costa Rica - Pérez Villanueva, Marta Eugenia (2021)
A monitoring study was carried out in two micro-catchments in the Reventazón basin, in Northern Cartago, Costa Rica; pesticide occurrence and water quality were analyzed. Twelve pesticides were detected, fve insecticides (chlorpyrifos, carbofuran, cypermethrin, imidacloprid, and oxamyl), four fungicides (carbendazim, imazalil, metalaxyl, and thiabendazole), and three herbicides (diuron, linuron, and terbutryn); eight of them presented risk quotients RQ >1, which implies a high risk for the environment. The water quality evaluation included fourteen physicochemical and microbiological parameters, out of which thermotolerant coliforms, nitrate, and total phosphorus exceeded a selected threshold value in every sample. Five metals were also included in the evaluation, Pb was the most frequent, followed by few detections of Cd, Cu, and Cr. Four water quality indexes (WQIs) were applied, two of them, the CCME WQI, based on physicochemical parameters, and the BMWP-CR WQI, based on benthic macroinvertebrate recount adapted to Costa Rican species, categorized all the sampling points as “bad” and “very bad” quality. This work of monitoring is important in the Latin American region, where there is a lack of information for regulation improvement and management decisions. These results showed poor management of the micro-catchments in this agricultural rural area.